Development And Evaluation Of Intervention Tools To Improve Primary School Teachers Knowledge On Asthma And Its Management In Penang, Malaysia - Khairunnisa, Khairunnisa (2012)

(untitled)
Primary school children who develop asthmatic attack during school hours required assistance from their teachers or school staff. Therefore teacher’s knowledge on asthma and its managements are vital in order for them to provide necessary assistance to their needy students. This scenario is particularly important in Malaysia as most primary schools do not have medically trained staff to assist students who develop medical problems during school hours.